E-READING II: Words database for reading by students from Basic Education II - de Oliveira, Adriana Marques [UNESP]; Capellini, Simone Aparecida [UNESP] (FapUNIFESP (SciELO), 2016)
Purpose: To develop a database of words of high, medium and low frequency in reading for Basic Education II. Methods: The words were taken from the teaching material for Portuguese Language, used by the teaching network of the State of São Paulo in the 6th to the 9th year of Basic Education. Only nouns were selected. The frequency with which each word occurred was recorded and a single database was created. In order to classify the words as of high, medium and low frequency, the decision was taken to work with the distribution terciles, mean frequency and the cutoff point of the terciles. In order to ascertain whether the words of high, medium and low frequency corresponded to this classification, 224 students were assessed: G1 (6th year, n= 61); G2 (7th year, n= 44); G3 (8th year, n= 65); and G4 (9th year, n= 54). The lists of words were presented to the students for reading out loud, in two sessions: 1st) words of high and medium frequency and 2nd) words of low-frequency. Results: Words which encompassed the exclusion criteria, or which caused discomfort or joking on the part of the students, were excluded. The word database was made up of 1659 words and was titled 'E - LEITURA II' ('E-READING II', in English). Conclusion: The E-LEITURA II database is a useful resource for the professionals, as it provides a database which can be used for research, educational and clinical purposes among students of Basic Education II. The professional can choose the words according to her objectives and criteria for elaborating evaluation or intervention procedures involving reading.
Keywords: Assessment; Education; Educational status; Learning; Primary schools; Reading; Schools; Secondary